UMA ANÁLISE ECONOMÉTRICA DA OFERTA AGRÍCOLA EM PERNAMBUCO - Bizarro dos Santos, Dinaldo; Alberto Brandt, Sérgio; Potsch Magalhães, Edson; Potsch Magalhães, Edson; Antonio da Cunha Viana, Luiz (Revista Econômica do Nordeste, 1982)
Acervo histórico